Mesoscale phase separation tough gel material and preparation method thereof

Prepared by physical blending and solvent evaporation method and forming a mesoscopic phase separation structure through metal ion crosslinking, the lack of research on the mesoscopic phase separation hydrogel materials in the prior art is solved, and gel material preparation with high mechanical properties is achieved, which is suitable for a variety of practical applications.

CN119912707AActive Publication Date: 2025-05-02NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI

Patent Information

Application Number
CN202510067640.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-05-02
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

In the prior art, there is still a lack of research on mesoscopic phase separation hydrogel materials, and it is difficult to control the characteristic length scale of phase separation. The preparation of mesoscopic phase separation hydrogels faces challenges.

Method used

The polymer film was prepared by physical blending and solvent evaporation, and a mesoscopic phase separation structure was formed by crosslinking metal ions to obtain a gel material with excellent mechanical properties.

Benefits of technology

The preparation of mesoscopic phase separation gel material has been realized, with high tensile strength, toughness and fracture toughness, and is suitable for flexible wearable devices, soft drivers and artificial muscles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912707A_ABST
    Figure CN119912707A_ABST
Patent Text Reader

Abstract

The invention discloses a mesoscale phase separation tough gel material, and belongs to the technical field of functional polymer materials, the mesoscale phase separation tough gel material comprises an island phase structure with the size of 0.1-5 microns and a continuous sea phase structure; wherein the island phase structure is obtained by crosslinking a copolymer of a hydrophilic monomer and a pyridine organic ligand through metal ions, and the marine phase structure is polyurethane; the mesoscale phase separation gel material based on the sea-island structure has abundant metal coordination and hydrogen-bond interaction, so that the gel has excellent load resistance and energy dissipation resistance and provides higher tensile strength. The invention also discloses a preparation method of the mesoscale phase separation tough gel material, the mesoscale phase separation tough gel material is prepared by adopting physical blending and solvent evaporation, the synthesis operation is simple, and the mesoscale phase separation tough gel material has wide application prospects in the fields of flexible wearable equipment, soft drivers, artificial muscles and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional polymer materials, and in particular relates to a mesoscopic scale phase separation strong and tough gel material and a preparation method thereof. Background Art

[0002] Hydrogels have important application value in the fields of biomedicine, flexible electronics, etc. Many of these applications require hydrogels to withstand mechanical loads and resist fracture under static or cyclic loading conditions. In order to improve the fracture energy of materials, people have developed and used a variety of strategies to improve the mechanical properties of hydrogels, including: 1. Topological structure design, such as slide-ring gels; 2. Introduction of sacrificial bonds for energy dissipation, such as double network hydrogels; 3. Introduction of higher-order structures, such as microphase separation structures and nanocrystalline domains. Among them, the microphase separation method can effectively combine the advantages of the two materials, while introducing energy dissipation units, further improving the strength and fracture energy of the gel material. Therefore, the development of the microphase separation method is expected to play a positive role in improving the mechanical strength and fracture toughness of the gel.

[0003] Phase separation is formed by the local aggregation of molecular segments. Block or random copolymers can stably produce a bicontinuous phase separation structure in the range of 5nm to 100nm. For example, polyampholyte hydrogels formed by dense and sparse polymer regions achieve improved fatigue resistance. However, this nanoscale (microscale) phase separation cannot produce a strong structure on a much larger scale than the polymer itself. In addition, they are also faced with the complexity of synthesis and the limitations of polymer types. Phase separation materials prepared by blending different polymers have poor compatibility due to differences in the physical or chemical properties of the polymers, resulting in phase separation on the scale of tens of microns. This macroscopic phase separation will damage the uniformity of the microstructure of the gel material and is not conducive to the improvement of mechanical properties.

[0004] Mesoscale phase separation structures ranging from hundreds of nanometers to several microns can be more evenly dispersed in the material, and the similar molecular structure causes it to form a more compact and strong phase structure. This strong phase separation structure provides the material with the ability to withstand loads and prevents the generation and expansion of cracks, thereby improving the fracture toughness of the material. However, due to the limitations of the preparation method, research on mesoscale phase separation hydrogels is still lacking. How to control the characteristic length scale of phase separation and prepare mesoscale phase separation hydrogels is a current challenge.

[0005] In the existing technology, researchers have developed a variety of methods for preparing strong and tough hydrogels, and have established a relatively solid foundation in the field of strong and tough integrated gel materials.

[0006] For example, the invention application with publication number CN118515902A discloses a strong composite hydrogel film, a preparation method and its application. The method uses biocompatible, biodegradable and non-toxic polyvinyl alcohol (PVA) and montmorillonite (MMT) as component elements, and prepares polyvinyl alcohol / montmorillonite (PVA / MMT) strong hydrogel through evaporation self-assembly technology. This composite hydrogel exhibits excellent mechanical properties, which solves the problem of insufficient mechanical properties of strong hydrogels in the prior art.

[0007] For another example, the invention application with publication number CN116925392A discloses a microphase-separated tough hydrogel with excellent anti-swelling properties and a method for preparing the same. By adopting a solvent exchange-assisted microphase separation strategy, polyvinyl alcohol (PVA) and polyurethane (PU) are first dissolved in dimethyl sulfoxide (DMSO) to form a mixed solution, and then DMSO is replaced by water through solvent exchange, and gelation occurs. During the gelation process, PVA macromolecules aggregate and undergo physical crosslinking, and PU macromolecules undergo phase separation to form microspheres, which are uniformly distributed in the hydrogel and have strong hydrogen bond interactions with PVA. Phase separation increases the crystallinity of PVA and reduces the distance between adjacent crystal domains. Rigid and stretchable PU microspheres and high crystallinity effectively improve the mechanical properties of the hydrogel. The preparation method of the invention is simple, and the obtained hydrogel has excellent mechanical properties, anti-swelling properties and biocompatibility.

[0008] However, there are currently very few strong and tough gel materials prepared based on mesoscopic scale phase separation, which makes it difficult to meet further practical applications. Summary of the invention

[0009] In view of the problems existing in the prior art, the present invention proposes a mesoscale phase separation tough gel material and a preparation method thereof. A polymer film with a mesoscale phase separation structure is obtained by physical blending and solvent evaporation, and further coordinated crosslinking with metal ions to obtain a mesoscale phase separation gel material with excellent mechanical properties.

[0010] A mesoscopic phase-separated tough gel material, comprising an island phase structure with a size of 0.1 to 5 microns and a continuous sea phase structure;

[0011] The island phase structure is a copolymer of a hydrophilic monomer and a pyridine organic ligand, obtained by cross-linking with metal ions; and the sea phase structure is polyurethane.

[0012] The present invention forms a hydrophilic polymer based on a hydrophilic monomer and a pyridine chelate ligand monomer. The metal ions and the hydrophilic polymer have good coordination ability. The strong coordination compound formed by cross-linking presents an island phase structure with a size of 0.1 to 5 microns. The island phase structure is evenly distributed in a continuous sea phase structure to form an island structure. The continuous sea phase structure has abundant hydrogen bond interactions inside, which provide the gel material with high tensile strength and energy dissipation capacity. The metal coordination and hydrogen bonding in the island phase structure make the gel have excellent load resistance and energy dissipation capacity, so that the strong and tough gel material based on the mesoscale phase separation has excellent mechanical properties.

[0013] Preferably, the mesoscopic phase separation tough gel material has a tensile strength of not less than 2.5 MPa and a toughness of not less than 20 MJ m-1 during stretching. 3 , fracture energy is not less than 5kJ m- 2 .

[0014] The present invention also provides a method for preparing a mesoscopic phase-separated tough gel material, comprising the following steps:

[0015] (1) dissolving a pyridine chelating ligand monomer, sodium hydroxide, a hydrophilic monomer and an initiator in deionized water, and then preparing a hydrophilic copolymer by thermally initiating free radical polymerization;

[0016] (2) dissolving a hydrophilic copolymer in deionized water and stirring the mixture to obtain a precursor solution 1, and dissolving a polyurethane in an organic solution and stirring the mixture to obtain a precursor solution 2;

[0017] (3) mixing the precursor solution 1 and the precursor solution 2, stirring them to obtain a mixed solution, and then obtaining a polymer film by a solvent evaporation method;

[0018] (4) Immersing the polymer film in step (3) in a solution containing metal ions to obtain a polymer hydrogel with mesoscale phase separation.

[0019] During the preparation process, the hydrophilic copolymer precursor solution and the polyurethane precursor solution are mixed, and the polymer film is obtained by solvent evaporation method, and then cross-linked with metal ions to form an island phase structure with a size of 0.1 to 5 microns. The final polymer hydrogel presents an island structure. When the tip stress is transmitted to the island phase structure, the expansion of the crack can be effectively prevented. This mesoscale phase separation is the main reason why the gel material has high tensile strength, toughness and fracture toughness.

[0020] Sodium hydroxide forms salts or ionic compounds with pyridine chelating ligand monomers, which increases the solubility of the chelating ligand monomers. In addition, it undergoes thermally initiated free radical polymerization with hydrophilic monomers to obtain hydrophilic copolymers. The chelating ligands in the copolymers can complex with metal ions, which can improve the strength and stability of the gel band.

[0021] Preferably, the pyridine chelating ligand monomer is at least one of ureidopyridine carboxylic acid, ureidopyridine carboxylic acid ester, and pyridine carboxylic acid;

[0022] The hydrophilic monomer is at least one of acrylamide and acrylic acid.

[0023] Preferably, the molar ratio of the pyridine chelating ligand monomer to the hydrophilic monomer is 1-4:100.

[0024] More preferably, the molar ratio of the pyridine chelating ligand monomer to the hydrophilic monomer is 1-2:100.

[0025] Preferably, the initiator is ammonium persulfate or potassium persulfate.

[0026] A suitable initiator is selected, and the polymerization reaction of the monomer molecules is promoted by inducing free radicals to obtain a linear hydrophilic copolymer.

[0027] Further preferably, in step (1), the mass percentage of the initiator in the pyridine chelate ligand monomer, sodium hydroxide, hydrophilic monomer and initiator is 1% to 2%.

[0028] In the process of preparing the gel material, the content of the initiator will affect the polymerization degree of the polymer. Selecting the initiator content within the above range to prepare the copolymer can make the hydrophilic copolymer have a suitable length and molecular weight.

[0029] Preferably, the thermally initiated free radical polymerization is carried out by oil bath heating, the oil bath heating temperature is 60° C. to 80° C., and the oil bath heating time is at least 2 hours.

[0030] The oil bath heating method is selected, and the monomers are excited to become monomer free radicals through the regulation of the two variables of temperature and time, thereby promoting the formation of hydrophilic copolymers.

[0031] Preferably, the mass percentage of the hydrophilic copolymer in the hydrophilic copolymer and the polyurethane is 5% to 15%.

[0032] Optionally, in step (2) and step (3), the stirring temperature is room temperature and the stirring time is at least 12 hours.

[0033] By adjusting the stirring time, each solute is mixed evenly in the solvent, so as to obtain a polymer film through a subsequent solvent evaporation method.

[0034] Optionally, in step (2), the organic solution is a mixed solution of ethanol and deionized water, wherein the volume ratio of ethanol to water is 19:1.

[0035] Preferably, the solvent evaporation method comprises casting the mixed solution obtained by stirring evenly into a polytetrafluoroethylene mold, and volatilizing the solvent at room temperature to obtain a polymer film; wherein the time for volatilizing the solvent at room temperature is at least 72 hours.

[0036] The water and organic solvent in the solvent are evaporated by the solvent evaporation method, so that the solution is in a supersaturated state, so that there is sufficient driving force for the growth of the polymer film. By adjusting the reaction time under constant temperature conditions to control the evaporation amount and thus the supersaturation of the solution, the resulting polymer film has uniform composition and a stable growth process, which can improve the stability of the gel material.

[0037] Preferably, the metal ion is at least one of zirconium ion, europium ion, terbium ion and zinc ion.

[0038] More preferably, the concentration of the metal ions is 0.1 mol / L to 1 mol / L.

[0039] The present invention also provides the use of the mesoscopic scale phase separation strong and tough gel material prepared by the preparation method in flexible wearable devices, soft actuators and artificial muscles.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) The continuous sea phase structure provides the gel material with high tensile strength and energy dissipation capacity. When the degree of stretching is further increased, the structure of the island phase will deform accordingly, thereby improving the tensile properties and toughness of the gel material.

[0042] (2) The island phase structures with a size of 0.1 to 5 microns are evenly distributed in the continuous sea phase structure. The island phase structure has excellent ability to resist load and energy dissipation. When the tip stress is transmitted to the island phase structure, the expansion of the crack can be effectively prevented, making this mesoscale phase separation gel material have high fracture energy.

[0043] (3) The present invention adopts physical blending and solvent evaporation methods to prepare mesoscopic phase-separated strong gel materials, and the synthesis operation is simple.

[0044] (4) The mesoscopic-scale phase-separated tough gel material provided by the present invention has broad application prospects in the fields of flexible wearable devices, soft actuators and artificial muscles. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1It is a schematic diagram of the internal structure of the mesoscopic scale phase separation strong and tough gel material.

[0046] Figure 2 This is a scanning electron microscope image of the mesoscopic scale phase separation tough gel material.

[0047] Figure 3 This is an optical picture of the mesoscopic scale phase-separated tough gel material prepared in Example 1 lifting a heavy object.

[0048] Figure 4 This is the stress-strain curve of the mesoscopic phase-separated tough gel material during stretching.

[0049] Figure 5 This is an optical photograph of a mesoscopic phase-separated tough gel material with a notch during stretching.

[0050] Figure 6 Schematic diagram of the mechanism of high fracture energy of mesoscopic phase-separated tough gel materials. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described and illustrated in detail below in conjunction with examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The operating methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The polyurethane used in the examples was purchased from AdvanSource Biomaterials, model number HydroMed D3.

[0052] The schematic diagram of the structure of the mesoscopic phase separation material prepared in the embodiment is as follows Figure 1 shown.

[0053] Example 1

[0054] A method for preparing a mesoscale phase-separated tough gel material comprises the following steps:

[0055] (1) First, 0.2 g of ureidopyridine carboxylic acid monomer, 0.109 g of sodium hydroxide, 4.8 g of acrylamide and 0.1 g of ammonium persulfate were dissolved in 50 mL of deionized water and reacted in an oil bath at 70° C. for 5 h to obtain a hydrophilic copolymer.

[0056] (2) 0.1 g of the hydrophilic copolymer was dissolved in 5.4 mL of deionized water and stirred at room temperature for 12 h to obtain a precursor solution 1; 0.9 g of the polyurethane was dissolved in an organic solution consisting of 0.3 mL of deionized water and 5.7 mL of ethanol and stirred at room temperature for 12 h to obtain a precursor solution 2.

[0057] (3) The precursor solution 1 and the precursor solution 2 prepared in step 2 are mixed and stirred for 12 hours to obtain a mixed solution.

[0058] (4) The mixed solution prepared in step (3) was dripped into a polytetrafluoroethylene mold (6×6 cm) using a dropper, and the solvent was evaporated at room temperature for 72 hours to obtain a polymer film.

[0059] (5) The polymer film was immersed in a 0.1 mol / L zirconium tetrachloride solution for 15 min and then transferred to deionized water to remove free zirconium ions to obtain a phase-separated polymer hydrogel.

[0060] The phase-separated polymer hydrogel prepared in this embodiment has a mesoscopic sea-island phase separation structure, such as Figure 2 And it can lift objects more than 6000 times its own weight, such as Figure 3 The tensile strength of the hydrogel in Example 1 is 3.3 MPa and the toughness is 28.8 MJ m -3 ,like Figure 3 The optical photograph of the notched sample during stretching is shown in Figure 5 As shown, the fracture energy is 13.7 kJ m -2 .

[0061] Example 2

[0062] The preparation steps of Example 2 are the same as those of Example 1, except that the molar ratio of the pyridine chelating ligand to the hydrophilic monomer is changed from 1:100 to 2:100. Specifically, 0.4 g of ureidopyridinecarboxylic acid monomer, 0.218 g of sodium hydroxide, 4.8 g of acrylamide and 0.1 g of ammonium persulfate are dissolved in 50 mL of deionized water.

[0063] Example 3

[0064] The preparation steps of Example 3 are the same as those of Example 1, except that the molar ratio of the pyridine chelating ligand to the hydrophilic monomer is changed from 1:100 to 4:100. Specifically, 0.8 g of ureidopyridinecarboxylic acid monomer, 0.436 g of sodium hydroxide, 4.8 g of acrylamide, and 0.1 g of ammonium persulfate are dissolved in 50 mL of deionized water.

[0065] Example 4

[0066] The preparation steps of Example 4 are the same as those of Example 1, except that the mass percentage of the hydrophilic copolymer in the polymer composed of the hydrophilic copolymer and the polyurethane is changed from 10% to 5%. Specifically, 0.05 g of the hydrophilic copolymer is dissolved in 5.4 mL of deionized water and stirred at room temperature for 12 h to obtain a precursor solution 1; 0.95 g of the polyurethane is added to a mixed solvent of 0.3 mL of deionized water and 5.7 mL of ethanol and stirred at room temperature for 12 h to obtain a precursor solution 2.

[0067] Example 5

[0068] The preparation steps of Example 5 are the same as those of Example 1, except that the mass percentage of the hydrophilic copolymer in all polymer components is changed from 10% to 15%. Specifically, 0.15 g of the hydrophilic copolymer is dissolved in 5.4 mL of deionized water and stirred at room temperature for 12 h; 0.85 g of the polyurethane is added to a mixed solvent of 0.3 mL of deionized water and 5.7 mL of ethanol and stirred at room temperature for 12 h.

[0069] Example 6

[0070] The preparation steps of Example 6 are the same as those of Example 1, with the only difference being that the metal ions are changed from zirconium ions to europium ions. Specifically, the polymer film is immersed in a 0.1 M europium nitrate solution for 15 min, and then transferred to deionized water to remove free europium ions to obtain a phase-separated polymer hydrogel.

[0071] Example 7

[0072] The preparation steps of Example 7 are the same as those of Example 1, except that the metal ions are changed from zirconium ions to terbium ions. Specifically, the polymer film is immersed in a 0.1 M terbium nitrate solution for 15 minutes and then transferred to deionized water to remove free terbium ions to obtain a phase-separated polymer hydrogel.

[0073] Example 8

[0074] The preparation steps of Example 8 are the same as those of Example 1, except that the hydrophilic monomer is changed from acrylamide to acrylic acid. Specifically, 0.2 g of ureidopyridinecarboxylic acid monomer, 0.109 g of sodium hydroxide, 4.9 g of acrylic acid and 0.1 g of ammonium persulfate are dissolved in 50 mL of deionized water, and reacted in an oil bath at 70° C. for 5 h to obtain a hydrophilic copolymer.

[0075] Example 9

[0076] The preparation steps of Example 9 are the same as those of Example 1, with the only difference being that the pyridine chelating ligand monomer is changed from a ureidopyridinecarboxylic acid monomer to a pyridinecarboxylic acid monomer. Specifically, 0.13 g of pyridinecarboxylic acid monomer, 0.109 g of sodium hydroxide, 4.8 g of acrylamide and 0.1 g of ammonium persulfate are dissolved in 50 mL of deionized water, and reacted in an oil bath at 70° C. for 5 h to obtain a hydrophilic copolymer.

[0077] Example 10

[0078] The preparation steps of Example 10 are the same as those of Example 1, with the only difference being that the metal ion concentration is changed from 0.1 mol / L to 0.5 mol / L. Specifically, the polymer film is immersed in a 0.5 mol / L zirconium tetrachloride solution for 15 min and then transferred to deionized water to remove free zirconium ions to obtain a phase-separated polymer hydrogel.

[0079] Embodiment 11

[0080] The preparation steps of Example 11 are the same as those of Example 1, with the only difference being that the metal ion concentration is changed from 0.1 mol / L to 1 mol / L. Specifically, the polymer film is immersed in a 1 mol / L zirconium tetrachloride solution for 15 min and then transferred to deionized water to remove free zirconium ions to obtain a phase-separated polymer hydrogel.

[0081] Comparative Example 1

[0082] The preparation steps of Comparative Example 1 are the same as those of Example 1, except that the mass percentage of the hydrophilic copolymer in the polymer composed of the hydrophilic copolymer and the polyurethane is changed from 10% to 20%. Specifically, 0.2 g of the hydrophilic copolymer is dissolved in 5.4 mL of deionized water and stirred at room temperature for 12 h to obtain a precursor solution 1; 0.8 g of the polyurethane is dissolved in an organic solution composed of 0.3 mL of deionized water and 5.7 mL of ethanol, and stirred at room temperature for 12 h to obtain a precursor solution 2.

[0083] Comparative Example 2

[0084] The preparation steps of Comparative Example 2 are the same as those of Example 1, except that the mass percentage of the hydrophilic copolymer in the polymer composed of the hydrophilic copolymer and the polyurethane is changed from 10% to 30%. Specifically, 0.3 g of the hydrophilic copolymer is dissolved in 5.4 mL of deionized water and stirred at room temperature for 12 h to obtain a precursor solution 1; 0.7 g of the polyurethane is dissolved in an organic solution composed of 0.3 mL of deionized water and 5.7 mL of ethanol, and stirred at room temperature for 12 h to obtain a precursor solution 2.

[0085] Comparative Example 3

[0086] The preparation steps of Comparative Example 3 are the same as those of Example 1, except that the polymer film is immersed in deionized water to reach swelling equilibrium, thereby obtaining a phase-separated polymer hydrogel.

[0087] Test Example 1

[0088] like Figure 3 , Figure 4 and Figure 5 As shown, the mechanical properties of the phase-separated polymer hydrogels prepared in each embodiment and comparative example were tested by weight pulling, stress-strain curve of tensile test and notched sample tensile test, and Table 1 shows the results of tensile strength, toughness and fracture energy of each embodiment and comparative example.

[0089] Table 1

[0090]

[0091]

[0092] The results show that the mesoscale phase separation strong and tough gel material has the characteristics of high tensile strength, high toughness and high fracture toughness. Its tensile strength is not less than 2.5MPa and its toughness is not less than 20MJ m -3 , fracture energy not less than 5 kJ m -2 .

[0093] This mesoscopic phase-separated gel material with high tensile strength and high toughness, when subjected to external tensile force, the sea phase composed of polyurethane provides the material with high tensile strength and energy dissipation capacity due to the rich internal hydrogen bond interactions. When the degree of stretching is further increased, the structure of the island phase will deform accordingly, which can also provide toughness to the material. Therefore, this mesoscale phase-separated strong gel material exhibits excellent tensile properties and toughness.

[0094] like Figure 6 As shown, based on this excellent mechanical property, a schematic diagram of the corresponding mechanism of fracture toughness is given. When the notched material is subjected to tension, the mesoscale island phase structure is evenly distributed in the sea phase structure. The metal coordination and hydrogen bonding in the island phase structure give it excellent ability to resist load and energy dissipation. Therefore, when the tip stress is transmitted to the island phase structure, the expansion of the crack can be effectively prevented, making this mesoscale phase separation gel material have high fracture energy.

Claims

1. A mesoscopic phase separation tough gel material, characterized in that: It includes island structures with a size of 0.1 to 5 microns and continuous marine structures; The island phase structure is obtained by cross-linking a copolymer of a hydrophilic monomer and a pyridine organic ligand through metal ions; The sea phase structure is polyurethane.

2. The mesoscopic phase separation tough gel material according to claim 1, characterized in that: The mesoscopic phase separation strong and tough gel material has a tensile strength of not less than 2.5 MPa and a toughness of not less than 20 MJ m- 3 , fracture energy is not less than 5kJ m- 2 .

3. The method for preparing a mesoscopic phase-separated tough gel material according to claim 1, characterized in that: The following steps are involved: (1) dissolving a pyridine chelating ligand monomer, sodium hydroxide, a hydrophilic monomer and an initiator in deionized water, and then preparing a hydrophilic copolymer by thermally initiating free radical polymerization; (2) dissolving a hydrophilic copolymer in deionized water and stirring the mixture to obtain a precursor solution 1, and dissolving a polyurethane in an organic solution and stirring the mixture to obtain a precursor solution 2; (3) mixing the precursor solution 1 and the precursor solution 2, stirring them evenly to obtain a mixed solution, and then obtaining a polymer film by a solvent evaporation method; (4) Immersing the polymer film in step (3) in a solution containing metal ions to obtain a polymer hydrogel with mesoscale phase separation.

4. The method for preparing a mesoscopic phase-separated tough gel material according to claim 3, characterized in that: The pyridine chelate ligand monomer is at least one of ureidopyridine carboxylic acid, ureidopyridine carboxylate, and pyridine carboxylic acid; The hydrophilic monomer is at least one of acrylamide and acrylic acid.

5. The method for preparing a mesoscopic phase-separated tough gel material according to claim 3, characterized in that: The molar ratio of the pyridine chelating ligand monomer to the hydrophilic monomer is 1-4:

100.

6. The method for preparing a mesoscale phase-separated tough gel material according to claim 3, characterized in that: The initiator is ammonium persulfate or potassium persulfate, and the mass percentage of the initiator in the pyridine chelate ligand monomer, sodium hydroxide, hydrophilic monomer and initiator is 1% to 2%.

7. The method for preparing a mesoscopic phase-separated tough gel material according to claim 3, characterized in that: The thermally initiated free radical polymerization adopts an oil bath heating method, the oil bath heating temperature is 60° C. to 80° C., and the oil bath heating time is at least 2 hours.

8. The method for preparing a mesoscopic phase-separated tough gel material according to claim 3, characterized in that: The mass percentage of the hydrophilic copolymer in the hydrophilic copolymer and the polyurethane is 5% to 15%.

9. The method for preparing a mesoscopic phase-separated tough gel material according to claim 3, characterized in that: The solvent evaporation method comprises pouring the mixed solution obtained by stirring evenly into a polytetrafluoroethylene mold, and volatilizing the solvent at room temperature to obtain a polymer film; wherein the time for volatilizing the solvent at room temperature is at least 72 hours.

10. The method for preparing a mesoscopic phase-separated tough gel material according to claim 3, characterized in that: The metal ion is at least one of zirconium ion, europium ion, terbium ion and zinc ion, and the concentration of the metal ion is 0.1 mol / L to 1 mol / L.

Citation Information

Patent Citations

  • Tough composite hydrogel film as well as preparation method and application thereof

    CN118515902A

  • PH sensitive medical polyurethane urea material and preparation method thereof

    CN108530606A

  • Novel gas-sensitive tracer material and method thereof

    CN116178620A

  • High-strength ionic liquid gel and preparation method thereof

    CN116655838A

  • Micro-phase separation tough hydrogel with excellent swelling resistance and preparation method thereof

    CN116925392A

Cited By

  • MXene and polyurethane synergistically modified micro-phase separation dual-network hydrogel as well as preparation method and application thereof

    CN121914500A

  • A microphase separation double network hydrogel synergistically modified by MXene and polyurethane, a preparation method and application thereof

    CN121914500B